Clinical pharmacology - Bennett, Perer N.; Brown, Morris J. (Morris Jonathan) (Edinburgh ; New York : Churchill Livingstone/Elsevier, 2008)
The item is Brand New Paperback International/South Asian Edition textbook with 100 % identical Contents as US Edition. Shipped Same Day. Will be dispatched fast. 100% Satisfaction. Great Customer Service, Buy with Confidence, Front Cover May Differ. Ships to PO or APO. May have printed "NOT FOR SALE OUTSIDE of INDIA" or Territorial Disclaimer.
Section 1 General -- Clinical pharmacology -- Topics in drug therapy -- Discovery and development of drugs -- Evaluation of drugs in humans -- Official regulation of medicines -- Classification of drugs and naming of drugs -- Section 2 From Pharmacology to Toxicology -- General pharmacology -- Unwanted effects of drugs: adverse reactions -- Poisoning, drug overdose, antidotes -- Drug abuse -- Section 3 Infection and Inflammation -- -- Chemotherapy of infections -- Antibacterial drugs -- Chemotherapy of bacterial infections -- Viral, fungal, protozoal and helminthis infections -- Drugs for inflammation and rheumatological disease -- Drugs and the skin -- Section 4 Nervous System -- Pain and analgesics -- Anaesthesia and neuromuscular block -- Psycotropic drugs -- Epilepsy, parkinsonism and allied conditions -- Section 5 Cardiorespiratory and Renal Systems -- Cholinergic and antimuscarinic (anticholinergic) mechanisms and drugs -- Adrenergic mechanisms and drugs -- Arterial hypertension, angina pectoris, myocardial infarction -- Cardiac arrhythmia and heart failure -- Hyperlipidaemias -- Kidney and urinary tract -- Respiratory system -- Section 6 Blood and Neoplastic Disease -- Drugs and haemostasis -- Cellular disorders and anaemias -- Neoplastic disease and immunosuppression -- Section 7 Gastrointestinal System -- Oesophagus, stomach and duodenum -- Intestines -- Liver, biliary tract and pancreas -- Section 8 Endocrine System, Metabolic Conditions -- Adrenal corticosteroids, antagonists, corticotrophin -- Diabetes mellitus, insulin, oral antidiabetic agents, obesity -- Thyroid hormones, antithyroid drugs -- Hypothalmic, pituitary and sex hormones -- Vitamins, calcium, bone
Includes bibliographical references and index.
Keywords: Clinical pharmacology; Pharmacology, Clinical